2022
DOI: 10.1155/2022/2379323
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Diversity of Bacteria Isolated from Fish and Fish Products Retailed in Kenyan Markets

Abstract: Fish products are highly vulnerable to microbial contamination due to their soft tissues, making them perishable and harmful to consumers. The clinical and subclinical infections reported by fish consumers are mainly associated with pathogenic microorganisms in fish products. Therefore, this study aimed at establishing the molecular profiles and diversity of the bacterial isolates from fish and fish products obtained from Kirinyaga County markets in Kenya. A total of 660 samples were randomly sampled in six Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
3
1
Order By: Relevance
“…was also isolated in this study. Our finding agrees with the findings of Domitila et al [25]. According to Setlow [27], the predominance of the Bacillus species can be attributed to their ubiquitous nature and the ability to produce endospores which allows them to survive in fish and fish processing conditions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…was also isolated in this study. Our finding agrees with the findings of Domitila et al [25]. According to Setlow [27], the predominance of the Bacillus species can be attributed to their ubiquitous nature and the ability to produce endospores which allows them to survive in fish and fish processing conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Bacterial infection has been a major challenge militating aquaculture and is responsible for high pond mortality, and it has been attributed as the main cause of economic losses [23,24]. Domitila et al [25], reported that based on Gram staining reaction, the majority of the bacterial isolates in their study were Gram-negative. On the other hand, Grampositive bacteria were also isolated in this study.…”
Section: Discussionmentioning
confidence: 98%
“…The percentage of Salmonella-positive samples (10.4%) in freshwater animal products was higher in the present study than in other studies [42]. Marine products including fresh carp, live grass carp, live bass, and Bellamya quadrata have been shown to be contaminated by Salmonella, indicating that aquatic products remain an important reservoir of Salmonella contamination and possible fecal contamination [43]. NTS outbreaks associated with chocolate consumption have occurred in multiple countries [44,45].…”
Section: Discussioncontrasting
confidence: 58%
“…This food can compromise the health of consumers if basic hygiene quality is not ensured. [40], Kyule et al [41], and Guetarni & Labdi [42] also revealed a diversity of bacteria isolated from fish in Kenya, Ghana, and Algeria, respectively. Proper processing methods are expected to considerably reduce pathogens [11] [43] [44].…”
Section: Discussionmentioning
confidence: 91%